1995
DOI: 10.1177/088610999501000106
|View full text |Cite
|
Sign up to set email alerts
|

Listening to the Voices of Battered Women: What Helps Them Escape Violence

Abstract: This article reports on a study that used focus groups to determine what helps battered women get out of their abusive relationships and survive and grow once they have left their abusers. The principles for social work practice with battered women that were derived from this research are based on the women's accounts of their experiences and of their needs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
43
0
2

Year Published

2001
2001
2017
2017

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 75 publications
(48 citation statements)
references
References 12 publications
3
43
0
2
Order By: Relevance
“…Participants who used shelters rated them to be "very" helpful and many described shelters as places where they finally felt safe: "The shelter is very helpful because I can sleep at night finally, and my son can sleep at night" (ID3). Moreover, consistent with previous research conducted with the non-Latina battered women (Davis & Srinivasan, 1995), a few of the Mexican-origin participants in this study described shelters as places where participants could be connected to other agencies, i.e., housing, childcare, and legal services.…”
Section: Formal Help-seeking "I Pressed Charges and That Was Freeingsupporting
confidence: 85%
“…Participants who used shelters rated them to be "very" helpful and many described shelters as places where they finally felt safe: "The shelter is very helpful because I can sleep at night finally, and my son can sleep at night" (ID3). Moreover, consistent with previous research conducted with the non-Latina battered women (Davis & Srinivasan, 1995), a few of the Mexican-origin participants in this study described shelters as places where participants could be connected to other agencies, i.e., housing, childcare, and legal services.…”
Section: Formal Help-seeking "I Pressed Charges and That Was Freeingsupporting
confidence: 85%
“…The "Power and Control/Equality Wheels" are popular educational tools of relationship dynamics used in domestic violence shelters and coalitions across the United States. Building upon prior work exploring and examining women's empowerment in the context of IPV (Busch & Valentine, 2000;Davis & Srinivasan, 1995;Gutierrez, et al, 1998;Kasturirangan, 2008), our findings underscore how empowerment is essential, as well, for nonviolent adult sons of abused women in stopping the cycle of violence. We developed the "Empowerment Wheel for Sons of Abused Women" (see Figure 1) as an educational and therapeutic tool for helping professionals to use with male witnesses to prevent the intergenerational transmission of violence.…”
Section: Discussionsupporting
confidence: 59%
“…However, not all battered women turn to shelters and advocacy organizations for help; in fact, most abused women seek help first from family and friends (Coker, Smith, Bethea, King, & McKeown, 2000;Davis & Srinivasan, 1995;Horton & Johnson, 1993) and then eventually from formal supports (Hutchison & Hirschel, 1998;Macy et al, 2005). Gordon's (1996) earlier review of the research on battered women's use of services suggested that the most commonly used social service systems were, in descending order of frequency, the criminal justice system (i.e., law enforcement and lawyers), social service agencies, medical services, crisis counseling, mental health services, clergy, and women's groups.…”
Section: Women's Experiences Of Getting Helpmentioning
confidence: 99%